Exacerbation of atopic dermatitis symptoms by ustekinumab in psoriatic patients with elevated serum immunoglobulin E levels: Report of two cases. Issue 6 (22nd March 2018) - Ishiuji, Yozo; Umezawa, Yoshinori; Asahina, Akihiko; Fukuta, Hirotaka; Aizawa, Norie; Yanaba, Koichi; Nakagawa, Hidemi
Abstract: Psoriasis is a chronic inflammatory skin disease mainly mediated by a T‐helper cell subset, Th17 cells. Recently, increased levels of total serum immunoglobulin (Ig)E have been reported in a subset of psoriatic patients. Ustekinumab (UST) is one of the most commonly used biologic agents for the treatment of moderate to severe plaque psoriasis, and a previous report also documented effectiveness of UST for psoriatic patients with high serum IgE levels. We experienced two psoriatic patients with high serum IgE levels, in whom UST completely improved psoriasis but paradoxically provoked or exacerbated atopic dermatitis (AD)‐like symptoms. This reciprocal phenomenon suggests the shift of Th balance toward Th2, along with altered profiles of inflammatory cytokines. It appears prudent to consider the possibility of such adverse effects when treating psoriatic patients with UST with concomitant AD symptoms, a history of AD or high serum IgE levels.